Report of Meeting. The Fourteenth Debrecen-Katowice Winter Seminar, Hajdúszoboszló (Hungary), January 29 - February 1, 2014 - AMSil, Redakcja (Annales Mathematicae Silesianae, 2014)
Report of Meeting. The Fourteenth Debrecen-Katowice Winter Seminar, Hajdúszoboszló (Hungary), January 29 - February 1, 2014.